2003
DOI: 10.1161/01.cir.0000050627.90734.ed
|View full text |Cite|
|
Sign up to set email alerts
|

Efferent Vagal Fibre Stimulation Blunts Nuclear Factor-κB Activation and Protects Against Hypovolemic Hemorrhagic Shock

Abstract: Background-We investigated whether electrical stimulation (STIM) of efferent vagus nerves may suppress nuclear factor (NF)-B activation and the inflammatory cascade in hemorrhagic (Hem) shock. Methods and Results-Rats were subjected to bilateral cervical vagotomy (VGX) or sham surgical procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
233
0
8

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 297 publications
(249 citation statements)
references
References 21 publications
6
233
0
8
Order By: Relevance
“…This indicates that the recently identified vagus nervemediated cholinergic antiinflammatory pathway (Borovikova et al, 2000;Guarini et al, 2003;Altavilla et al, 2006;Tracey, 2007) is involved in the neuroprotective effect of melanocortins against ischemic stroke, as it occurs in circulatory shock and myocardial ischemia (Guarini et al, 2004;Mioni et al, 2005).…”
Section: Discussionmentioning
confidence: 93%
“…This indicates that the recently identified vagus nervemediated cholinergic antiinflammatory pathway (Borovikova et al, 2000;Guarini et al, 2003;Altavilla et al, 2006;Tracey, 2007) is involved in the neuroprotective effect of melanocortins against ischemic stroke, as it occurs in circulatory shock and myocardial ischemia (Guarini et al, 2004;Mioni et al, 2005).…”
Section: Discussionmentioning
confidence: 93%
“…10,14 The a7nAChR can be considered to be a peripheral 'immune' component of the cholinergic anti-inflammatory pathway. 18,19 Molecular mechanisms supporting these anti-inflammatory effects include nuclear factor kappa B pathway inhibition, 20 activation of Janus activated kinase --signal transducer and activator of transcription 21 and the consequent inhibition of TNFa production. 22 A functional role of nicotinic acetylcholine receptors (nAChRs) has already been demonstrated in rat adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory cytokines plays an important role in acute hypovolemic hemorrhagic shock because anti-TNF-α monoclonal antibodies could increase survival, improve hypotension, and attenuate impairment in vascular reactivity [32] . Recent studies have demonstrated that electrical stimulation of efferent vagal fibers could rapidly reverse hypotension, counteract hepatic NF-κB activation, reduce TNF-α plasma levels and improve survival rate in experimental hemorrhagic shock rats [13,33] . Systemic administration of an acetylcholinesterase inhibitor also improves outcomes after hemorrhagic shock [22] .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that activation of the α7nAChR-dependent cholinergic anti-inflammatory pathway can control the production of proinflammatory cytokines in experimental models of endotoxic shock and hemorrhagic shock [12,13] . Our previous studies have shown that anisodamine blocks muscarinic receptors and promotes increased endogenous acetylcholine binding to the α7nAChR [6] .…”
Section: Introductionmentioning
confidence: 99%